Echoes of resistance - Ubhenin, Oscar Edoror (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2015)
This article recognizes the gap in existing literature, regarding the capability of social groups in resistance to mass violence. The basic assumption of this article is that social groups as networks could serve as platforms of resistance to mass violence, regardless of their organizational goals and objectives. In order to explore this fundamental assumption, one research question was formulated: what is the utility of social groups in resisting mass violence? In a bid to provide an answer to this question, the article analyses the religious affiliation, geographical location and spread, ethnic stock and dynamics of selected social groups in Nigeria. The article is based on a review of academic articles, published newspaper reports and articles, and commonly used reports from the human rights circle. The article notes the linkage between social groups, on one hand, and prejudices, fears, and identities within societies, on the other. It recommends empowerment, which would allow social group members to find paths towards the solution to the problem of mass violence.
Keywords: etnični konflikti; verski konflikti; genocid; množično nasilje; odpor; družbene skupine; Nigeria; Nigerija